Predation of brown-eared anole Norops fuscoauratus (Squamata: Dactyloidae) by the woolly mouse opossum Marmosa demerarae (Didelphimorphia: Didelphidae) - Merces, Michelle Pinto; Alves-Silva, Kleiton Rodolfo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The woolly mouse opossum Marmosa demerarae is an omnivorous species that primarily feeds on insects and fruits. Knowledge over the natural history of this species remains incipient. In the literature, there is only one record of M. demerarae feeding on vertebrates, which was caused by human intervention. We present the first record of M. demerarae predation on the brown-eared anole Norops fuscoauratus in the municipality of Barcarena, state of Pará, Brazil. This record is relevant for obtaining more detailed information on M. demerarae feeding ecology in the Amazon.
Keywords: Amazon; Diet; Marsupial; New record